2019
DOI: 10.1016/j.foot.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of manual therapy on gastrocnemius muscle stiffness in healthy individuals

Abstract: Study Design: Randomized clinical trial. Background: Muscle stiffness is a potential complication after injury and has been shown to be a risk factor for injury in healthy individuals. Objectives: The primary purpose of this study was to assess the short-term effects of manual therapy (MT) on muscle stiffness of the gastrocnemius in both a relaxed and contracted state. The secondary purpose was to assess the reliability of a novel clinical tool (MyotonPRO) to measure muscle stiffness in the gastrocnemius in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…On the other hand, the myotonometry usefulness in order to evaluate the muscle stiffness seems to be doubtless 32 . Moreover, some studies have linked stiffness with sport-related injuries [54][55][56] . Only one study from Ditroilo et al 57 was found in order to compare myotonometry data with population from the current study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the myotonometry usefulness in order to evaluate the muscle stiffness seems to be doubtless 32 . Moreover, some studies have linked stiffness with sport-related injuries [54][55][56] . Only one study from Ditroilo et al 57 was found in order to compare myotonometry data with population from the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Reliability of the MytonPRO in a resting state has been shown to be 0.99 to 1.0 13 and in a contracted state in a standing position within day ICC was 0.94 and between day ICC was 0.99. 14…”
Section: Myotonometrymentioning
confidence: 99%
“…Taking these factors into account, our results are largely consistent with the current literature. For example, in healthy participants, it was shown that manual therapy can reduce muscle stiffness [132]; this was demonstrated for MET [133], MRT (or self-MRT, respectively, which mimics manual MRT with a foam roller) [134], and STT (or massage, respectively, which resembles STT using deep pressure gliding strokes) [135]. Similarly, it was revealed that trigger points have an increased muscle tone and stiffness [113], which can be decreased through manual myofascial release [136].…”
Section: Discussionmentioning
confidence: 99%